Book Review of â€œThe Origins of Social Work: Continuity and Changeâ€. Basingstoke: Palgrave Macmillan, 2005, by Malcolm Payne - John Schmoller (Social Work and Society)
Malcolm Payneâ€™s latest work proposes to survey the continuity and change in social work from its inception and origins, up until the present day. In order to do justice to the theme, its author could have concentrated on developing a narrative of a national enterprise, or restricted himself to a regional analysis (Western European Social Work) or opt instead for a more narrowly focused cultural exploration, White Anglo-Saxon Social Work (WASSW). One can only infer that limiting himself in this fashion would have struck the author as parochial, or rather, that only a truly global enterprise could satisfy his capacious mind. One is left to marvel at the invocation of Darwinâ€™s great work and wonder what was the process of the authorâ€™s â€œnaturalâ€ selection of this material.